Management learning and the greening of SMEs: Moving beyond problem-solving - Debbie Millard (Zeitschrift für Personalforschung (ZfP), 2011)
Win-win and eco-efficiency approaches to environmental management that focus on cost benefits from environmental improvement in business have been widely promoted in recent years. However they have been criticized because they are of limited appeal to small and medium sized enterprises (SMEs) and because they do not promote a broader programme of learning and change. Based on qualitative interviews with SMEs in the UK that have participated in a resource efficiency project, the paper aims to identify the conditions under which management learning is occurring, that triggers a process of on-going environmental improvement. The main indicators of management learning identified that lead to a process of learning and change were: cognitive and behaviour change; an approach that went beyond problem-solving; a culture of leadership and participation; a discontinuity that made resource efficiency a priority; a networked, open-minded leader. – – Win-win- und Ökoeffizienz-Ansätze im Umweltmanagement, die auf die Kosteneinsparung durch Umweltmanagement setzen, wurden in den letzten Jahren verstärkt empfohlen. Sie werden allerdings kritisiert, da sie auf wenig Interesse bei Klein- und Mittleren Unternehmen (KMU) stoßen und nicht unbedingt organisationales Lernen und Organisationsveränderung fördern. Basierend auf qualitativen Interviews mit Vertretern von KMU in Großbritannien, die an einem Ressourceneffizienz-Projekt teilnahmen, identifiziert dieser Aufsatz Bedingungen, unter denen organisationales Lernen stattfindet und ein kontinuierlicher Verbesserungsprozess des Umweltmanagements gefördert wird. Die Hauptfaktoren, die organisationales Lernen fördern und zu einem Prozess des Lernens und der Veränderung führen, waren: Kognitive und Verhaltensänderungen; eine Überwindung des Problemlösungsfokus; eine Kultur der Führung und Partizipation; eine Diskontinuität, die Resourceneffizienz prioritär macht; ein vernetzter, aufgeschlossener Geschäftsführer.
Keywords: M12; M14; M54; Q01; 330; greening; resource efficiency; SMEs; learning; Öko-Effizienz; Kostenmanagement; Lernende Organisation; KMU; Großbritannien